Hardware-in-the-loop Simulation Platform for Traction Drive System Adhesion Control Based on dSPAC - WANG Sai; YANG Zhong-ping; LIN Fei; SUN Hu (机车电传动)
On the basis of analyzing adhesion force generation mechanics, wheelset driving mechanism and vehicle dynamic model, a vehicle dynamics hardware-in-the-loop (HIL) simulation method used for adhesion control study was proposed and verified by experiment based on dSPACE. Furthermore, an adhesion control method based on slip velocity was tested on the HIL simulation platform.